Developing a method to generate an adaptive real-time camouflage pattern based on electro-chromic active devices - Nguyễn, Thành Lâm; Nguyen, Anh Tuan; Nguyen Manh Thang (Journal of Military Science and Technology, 2024)
Traditional camouflage faces limitations in modern combat, especially with moving targets or rapidly changing backgrounds. Adaptive camouflage, which adjusts colors and patterns in real time, provides a more flexible and effective solution. This paper presents a comprehensive study of popular adaptive camouflage principles worldwide and proposes a camouflage model for the visible light spectrum based on active electro-chromic principles. Evaluation results indicate that adaptive patterns achieve the lowest Camouflage Similarity Index (CSI) and the highest Universal Image Quality Index (UIQI) across various backgrounds, demonstrating the clear effectiveness of the proposed model. With 3 to 5 dominant colors, pattern generation time is under 1 second, and adaptive patterns exhibit the highest similarity to the background compared to fixed patterns.